Understanding physical literacy in the context of health: a rapid scoping review - Katie Cornish; Gloria Fox; Trina Fyfe; Erica Koopmans; Anne Pousette; Chelsea A. Pelletier (BMC, 2020)
Abstract Background Physical literacy is a multidimensional concept that describes a holistic foundation for physical activity engagement. Understanding the utilization and effectiveness of physical literacy in the context of health and the health care setting will support clinical and population health programming. The purpose of this rapid scoping review was to: 1) map the conceptualization of physical literacy as it relates to health; 2) identify and describe the utilization of physical literacy in the context of health and engagement of health care providers; and 3) better understand the relationship between physical literacy, physical activity, and health. Methods Following established scoping review methods adapted for a rapid review approach, we searched electronic databases Medline OVID, CINAHL Ebsco, PsycInfo Ebsco, Web of Science ISI, and ERIC Ebsco from conception until September 2019. Tabulation coding was used to identify the key themes across included articles and synthesize findings. The review follows an integrated knowledge translation approach based on a partnership between the health system, community organizations, and researchers. Results Following removal of duplicates, our search identified 475 articles for title and abstract screening. After full text review, 17 articles were included (12 original research papers and five conceptual or review papers). There was near consensus among included papers with 16 of 17 using the Whiteheadian definition of physical literacy. There was limited involvement of health care providers in the concept of physical literacy. Physical literacy was connected to the following health indicators: BMI and body weight, waist circumference, cardiorespiratory fitness, physical activity, and sedentary behaviour. The primary demographic focus of included studies was children and there was a conceptual focus on the physical domain of physical literacy. Conclusions Despite growing popularity, the empirical evidence base linking physical literacy and health outcomes is limited and the relationship remains theoretical. Physical literacy may present a novel and holistic framework for health-enhancing physical activity interventions that consider factors vital to sustained participation in physical activity across the life course. Future work should continue to explore the nature and direction of the relationship between physical activity and physical literacy to identify appropriate focused approaches for health promotion.